Growth differentiation factor 15 as a prognostic marker in patients with acute myocardial infarction. (22nd September 2015) - Khan, SQ; Ng, K; Dhillon, O; Kelly, D; Quinn, P; Squire, IB; Davies, JE; Ng, LL
Abstract : Background: Our aim was to assess the long-term prognostic value of growth differentiation factor 15 (GDF-15) in patients post acute myocardial infarction (AMI). GDF-15 is a member of the transforming growth factor beta family. GDF-15 is expressed in the myocardium and upregulated due to "stress" and has been shown to have antiapoptotic actions. Its role in the cardiovascular system, however, is not well defined. We were interested to see if GDF-15 could provide long-term prognostic value in post-AMI patients. We compared GDF-15 with N-terminal pro-B-type natriuretic peptide (NT-proBNP). Methods: We recruited 1142 consecutive post-AMI patients (820 men, median (range) age 67 years (24–97)) in a prospective study with a follow-up period of 505 days (range 1–2837). Plasma measurements were made 3–5 days after chest pain onset. NTproBNP and GDF-15 levels were determined using an in-house non-competitive immunoassay. Patients were followed up for the combined endpoint of death or heart failure. Results: There were 140 (12.3%) deaths and 113 (9.9%) readmissions with heart failure. GDF-15 levels increased with increasing Killip class (p<0.001) and were correlated with NT-proBNP (r  =  0.57, p<.001). Using a multivariable Cox proportional hazards model log GDF-15 (hazard ratio (HR) 1.80), log NT-proBNP (HR 2.19), age (HR 1.03) Killip class above 1 (HR 1.68) were significant independent predictors of death or heart failure. Predictors of death were log NT-proBNP, log GDF-15, age, estimated glomerular filtration rate, past history of myocardial infarction. The C-statistic for GDF-15 for predicting death or heart failure at 1-year was 0.73 (95% CI 0.70 to 0.76, p<0.001) and was 0.76 (95% CI 0.70 to 0.80, p<0.001) for NT-proBNP. Combining these markers yielded an area under the curve (AUC) of 0.81 (95% CI 0.77 to 0.85), which exceeded that of GDF-15 (p<0.001) and NT-proBNP (p = 0.004) alone. The Kaplan–Meier analysis revealed that those patients with above median GDF-15 and NT-proBNP had the highest event rate for death and heart failure (log rank 50.22, p<0.001). Conclusions: GDF-15 is a new marker for predicting death and heart failure in post-AMI patients. GDF-15 provides prognostic information over and above clinical factors and the established biomarker NT-proBNP. Combined levels of GDF-15 with NT-proBNP can identify a high-risk group of patients.